2011
DOI: 10.1111/j.1440-1754.2011.02230.x
|View full text |Cite
|
Sign up to set email alerts
|

Bony presentations of childhood haematological malignancy to the emergency room

Abstract: The diagnosis of childhood haematological malignancy with first bony presentation to the ER was challenging, with a high prevalence of 71.4% undiagnosed cases at first visit. We highlight the common misdiagnoses because failure to correctly diagnose could delay timely institution of treatment. Trauma or normal investigations do not exclude an underlying haematological malignancy. This rare diagnosis in the ER should always be considered when challenged with recurrent bony complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The timing of various presentations may be related to the burden of leukemic cells: the leukaemia burden at an early stage of leukaemia is small and may only affect the haematological system or surrounding osteoarticular tissues. Previous studies, primarily case‐only reports, have also suggested haematological and musculoskeletal presentations as signs of leukaemia and to our knowledge our report is the first to quantify these associations. Additionally, we demonstrated the timing of these and other less specific presentations, including respiratory, gastrointestinal and urinary tract presentations, and injuries.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The timing of various presentations may be related to the burden of leukemic cells: the leukaemia burden at an early stage of leukaemia is small and may only affect the haematological system or surrounding osteoarticular tissues. Previous studies, primarily case‐only reports, have also suggested haematological and musculoskeletal presentations as signs of leukaemia and to our knowledge our report is the first to quantify these associations. Additionally, we demonstrated the timing of these and other less specific presentations, including respiratory, gastrointestinal and urinary tract presentations, and injuries.…”
Section: Discussionmentioning
confidence: 55%
“…Clinical studies have reported some presentations before or at the time of leukaemia diagnosis, such as fever, anaemia, bleeding or musculoskeletal discomfort . Researchers have also attempted to summarise the duration between initial presentations and leukaemia diagnosis in case series .…”
Section: Introductionmentioning
confidence: 99%
“…The prompt recognition and early correct diagnosis of acute leukemia may prove to be a good prognostic feature of childhood acute leukemia. [8] This is also true for the acute leukemia in adults. [9] Septic arthritis is a medical and surgical emergency that, if left untreated, may lead to permanent joint disfigurement and loss of function.…”
Section: Discussionmentioning
confidence: 90%
“…This may cause difficulty in establishing a diagnosis because patients may seek orthopedic or emergency treatment initially. [1,2,4] Teo et al [8] also reported that the diagnosis of childhood hematological malignancy with first bony presentation to the emergency room was challenging, with a high rate of undiagnosed cases (71.4% at first visit). Failure to diagnose hematological malignancy correctly may delay timely institution of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of systemic signs, musculoskeletal presentations of malignancies may not be easily recognised and pose as a diagnostic challenge even to the most experienced clinicians. In a sutudy, the prevalence of bony complaints as the first presentation of childhood haematological malignancy was reported as 14.2% and the diagnosis of malignancy was challenging with a high rate of undiagnosed cases at 71.4% at first visit 11 . Our patient was initially diagnosed as osteomyelitis in another center with the complaints of knee pain and swelling and could be diagnosed as NHL after 11-month-delay during an investigation of abdominal pain, probably originated from enlarged and conglomerated lymph nodes caused by tumoral infiltration.…”
Section: Discussionmentioning
confidence: 99%